Arah Kebijakan Arah Kebijakan Pengembangan SDM: Arah Kebijakan Pengembangan SDM - Ariska Putri Mase; Ilham Tahier; Nur Ainun; Rezky Ramadhani; Satriani Satriani; Nurmala Nurmala (RESEARCH FAIR UNISRI, 2024)
This article will discuss and analyze the current direction of human resource development policy. The method for writing this scientific article uses literature study / Library Research. This research aims to find out and analyze the current direction of human resource development. Human resource development can be understood as the preparation of individual employees to assume different or higher responsibilities within the organization. Therefore, human resources really determine the process of successful performance of an organization. Human resource development aims to make it easier to realize organizational goals, because quality human resources are considered capable of carrying out their duties and functions as employees in an organization. This research examines the meaning of human resource development, benefits, objectives, forms, methods, strategies and steps in human resource development.